2015
DOI: 10.1590/s1517-838246120130657
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi from medicinal plant Bauhinia forficata: Diversity and biotechnological potential

Abstract: Bauhinia forficata is native to South America and used with relative success in the folk medicine in Brazil. The diversity, antibacterial activity, and extracellular hydrolytic enzymes of endophytic fungi associated with this plant were studied. Plant samples, which included leaves, sepals, stems, and seeds, were used. Ninety-five endophytic fungal were isolated (18 from leaves, 22 from sepals, 46 from stems, and nine from seeds), comprising 28 species. The most frequently isolated species were Acremonium curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 46 publications
2
63
0
1
Order By: Relevance
“…Studies with endophytic fungi have isolated most frequently fungi from stem than from leaves, unlike that observed in C. lechleri (Banhos et al, 2014;Bezerra et al, 2015). Other studies showed leaves with the highest colonization of endophytic fungi (Souza et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies with endophytic fungi have isolated most frequently fungi from stem than from leaves, unlike that observed in C. lechleri (Banhos et al, 2014;Bezerra et al, 2015). Other studies showed leaves with the highest colonization of endophytic fungi (Souza et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The relative frequency of isolation (RF) was calculated as the number of isolates of a species divided by the total number of isolates, being expressed as a percentage (Bezerra et al, 2015). For the diversity analysis of the endophytic community of C. lechleri, the Simpson and Shannon indices were used to calculate the number of dominant species (Bezerra et al, 2015).…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
See 3 more Smart Citations